2022
DOI: 10.3389/fmicb.2022.1051575
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of a urine-based ELISA assay for the screening of human schistosomiasis japonica: A comparative study

Abstract: The current study developed and evaluated the performance of a urine-based enzyme-linked immunosorbent assay (ELISA) for the screening of Schistosoma japonicum infection in a human cohort (n = 412) recruited from endemic areas, Northern Samar, the Philippines. The diagnostic performance of the urine ELISA assay was further compared with the Kato-Katz (KK) technique, serum-based ELISA assays, point-of-care circulating cathodic antigen (POC-CCA) urine cassette test, and droplet digital (dd)PCR assays performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The human cohort had a moderate schistosomiasis japonica prevalence (26.2%) but a low intensity of infection based on the KK analysis on faecal samples (6 slides on two stool samples), according to the categorization by WHO. Detailed information of the study cohort can be found in previous studies ( 18 , 51 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…The human cohort had a moderate schistosomiasis japonica prevalence (26.2%) but a low intensity of infection based on the KK analysis on faecal samples (6 slides on two stool samples), according to the categorization by WHO. Detailed information of the study cohort can be found in previous studies ( 18 , 51 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study recruited human subjects from 18 barangays moderately endemic (27% prevalence) for schistosomiasis japonica in the municipalities of Laoang and Palapag, Northern Samar, Philippines, in 2015 ( 3 , 18 , 39 , 42 ). Fecal and serum samples were collected from the participating subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Several immunologic tests, including the indirect hemagglutination assay (IHA), enzyme-linked immunosorbent assay (ELISA), and rapid diagnostic tests (RDTs), have proven to be cost-effective and have been extensively employed for infection control and transmission control purposes (Lv et al 2022). However, they may face challenges related to lower specificity when utilizing crude extracted antigens and the difficulty of distinguishing between past and present infections (Mu et al 2023b). Furthermore, the use of nucleic acid-based diagnostic methods has shown higher performance in detecting various schistosome species, especially in low-level infections.…”
Section: Introductionmentioning
confidence: 99%